Analysis of the Engagement Characteristic of Spring Clutch under Different Pre Expansion Quantity - Zhao Peng; Yan Hongzhi; Xia Fan; Cao Yuming; Chen Xinyu (Jixie chuandong)
The pre expansion quantity of the spring directly affects the dynamic and static performance of spring clutch. On the basis of establishing the spring clutch dynamics finite element model,the dynamic engagement characteristic of spring under the different condition of pre expansion quantity is analyzed,the response time,radial displacement and inner ring joint time and spring Mises stress and compressive stress are obtained. The results indicate that spring and shell cannot stable engaging when have no pre expansion quantity,and it would lead to invalidation. In a stable engagement condition,the engagement and response time is in milliseconds. Increasing the pre expansion quantity,the spring radial displacement increases,the average compressive stress of spring along the length direction would decrease,and the distribution of compressive stress becomes more uniform.